A general correlation for the stagnation point Nusselt number of an axisymmetric impinging synthetic jet - MURRAY, DARINA; PERSOONS, TIM (My University, 2011)
Whereas the heat transfer mechanisms in steady impinging jets are well understood, the available knowledge of heat transfer to impinging synthetic jets remains inconsistent. This paper provides an objective comparison of the stagnation point heat transfer performance of axisymmetric impinging synthetic jets versus established steady jet correlations. Furthermore, a general correlation for the stagnation point Nusselt number is proposed including the effect of all appropriate scaling parameters: Reynolds number (500 ? Re ? 1500), jet?to?surface spacing (2 ? H/D ? 16) and stroke length (2 ? L0/D ? 40). Based on the ratio of stroke length to jet?to?surface spacing L0/H, four heat transfer regimes are identified.
PUBLISHED
Keywords: Thermal engineering; impinging jet; forced convection; synthetic jet formation; Smart & Sustainable Planet; Telecommunications